Подвижные микроорганизмы – сенсоры высокочастотного электромагнитного и биологического поля - Караченцева, А.И.; Левчук, Ю.Н. (Биополимеры и клетка, 1989)
У подвижных эукариот (Dunaliella viridis) и прокариот (Escherichia coli) обнаружена способность к восприятию высокочастотного электромагнитного поля и излучения ладони руки человека-индуктора. У рухливих еукаріотів (Dunaliella viridis) і прокаріотів (Escherichia coli) виявлено здатність до сприйняття високочастотного електромагнітного поля і випромінювання долоні руки людини-індуктора. The ability to receive electromagnetic microwaves has been revealed in prokaryotic (Escherichia coli) and eukaryotic (Dunaliella viridis) cells, mm-range generator and the skin of man's hand are used as the sources of microwaves. Reception of mm-field by cells results in their collective directed motion: negative radiotaxis. Special experiments have showed that radioreception is not connected with thermal influence of microwaves.